2013
DOI: 10.14202/vetworld.2013.803-806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aloe vera on dressing percentage and haemato-biochemidal parameters of broiler chickens

Abstract: Aim:To evaluate the effects of Aloe vera on dressing percentage and hemato-biochemical parameters of broiler chickens. Materials and Methods:A total of 90 chicks were used in this study. They were randomly allocated into 3 treatment groups. Fresh Aloe vera leaf juice (ALJ) was prepared and administered to the test group T3 at the rate of 20 g/L in drinking water daily. This study was carried out for 42 days. Dressing percentage and hemato-biochemical parameters were recorded at the end of experiment.Results: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
4
12
3
Order By: Relevance
“…control, basal diet; basal diet with 0.5% nettle; basal diet with 1% nettle; basal diet with 2% nettle ( Safamehr et al., 2012 ). According to Singh et al. (2013) who had done research on Effects of Aloe vera on dressing percentage and haemato-biochemical parameters of broiler chickens showed no significant result was obtained in the levels of total protein, albumin, globulin, A/G ratio amongst all the groups which match the current research.…”
Section: Discussionsupporting
confidence: 69%
“…control, basal diet; basal diet with 0.5% nettle; basal diet with 1% nettle; basal diet with 2% nettle ( Safamehr et al., 2012 ). According to Singh et al. (2013) who had done research on Effects of Aloe vera on dressing percentage and haemato-biochemical parameters of broiler chickens showed no significant result was obtained in the levels of total protein, albumin, globulin, A/G ratio amongst all the groups which match the current research.…”
Section: Discussionsupporting
confidence: 69%
“…The results of the present study with respect on PCV were in agreement with Mmereole et al, (2011) evaluate the effect of dietary inclusion of Aloe the results of PCV count of experimental birds showed that there were significant (p<0.05) difference in haematological parameters among different diet groups, also Singh et al, (2013) had reported that fresh Aloe vera leaf juice (20g/L) significantly (p<0.05) higher PCV value than other treatment groups. Esonu et al, (2006) feeding Neem (Azadirachta indica) leaf meal (NLM) birds fed diet with 10 per cent Neem leaf meal recorded the highest haemoglobin value of 12.0g/100ml, packed cell volume (PCV) of layers in the 10 per cent treatment group differed significantly from that control treatment group, similarly Ansari et al, (2012) and Bonsu et al, (2012) Obikaonu et al, (2012 fed on diets containing antibiotic and leaf meal had higher (p<0.05) PCV over other treatment groups.…”
Section: Packed Cell Volumesupporting
confidence: 89%
“…The present study results presented enhanced blood total protein and albumin levels in birds treated with Aloe vera gel in drinking water. The blood total protein and albumin had higher values in birds treated with 1.5% Aloe vera gel than the control, which contradict Singh and Koley (27) and Sharma and Singh (13), who stated no significant differences among the birds fed dietary Aloe vera. The contradicting results are probably attributed to the differences in the addition of Aloe vera wherein it was supplied in drinking water in the present study while Singh and Koley (27) and Sharma and Singh (13) included Aloe vera as dietary additives.…”
Section: Discussioncontrasting
confidence: 63%